Barium Titanate Functionalization with Organosilanes: Effect on Particle Compatibility and Permittivity in Nanocomposites - Nico Zamperlin; Andrea Bottacini; Emanuela Callone; Alessandro Pegoretti; Marco Fontana; Sandra Dirè (Molecules, 2022)
Barium titanate (BT) recently gained new interest in the preparation of dielectric and piezoelectric lead-free materials for applications in sensors, electronics, energy harvesting and storage fields. Barium titanate nanocomposites can achieve attractive performance, provided that the compatibility between ceramic particles and polymeric matrices is enhanced to the benefit of the physical properties of the final composite. Tuning the particle–matrix interface through particle functionalization represents a viable solution. In this work, surface functionalization of BT nanoparticles (NPs), obtained by hydrothermal synthesis, with 3-glycidyloxypropyltrimethoxysilane, 2-[(acetoxy(polyethyleneoxy)propyl]triethoxysilane and triethoxysilylpropoxy(polyethyleneoxy)dodecanoate, was performed after optimizing the hydroxylation process of the NPs to improve their surface reactivity and increase the yield of grafting. Solid-state nuclear magnetic resonance and thermogravimetric analysis were used to quantify the molecules grafted onto the ceramic nanoparticles. Both bare and functionalized particles were employed in the realization of epoxy- and polydimethylsiloxane (PDMS)-based nanocomposites. Functionalization was proven to be beneficial for particle dispersibility and effective for particle alignment in the PDMS matrix. Moreover, the dielectric constant measurements revealed the potential of PDMS-based nanocomposites for applications in the field of dielectric elastomers.